Description of operations management practices applied to hospital services management: a literature review - Sánchez Suárez, Yasniel (2022)
The management of hospital institutions is becoming more and more complex. The current situation requires abandoning functional management models for operational ones that integrate preventive, curative, and managerial functions efficiently to raise the quality of care. This article analyzes the evolution of process management practices in the administration of hospital services. Bibliographic and documentary review, participatory scientific observation, interviews, and observation of the processes are used to determine key variables for the analysis of models, complemented with a descriptive quantitative bibliometric analysis of the main applications of the functions of operations management in hospital systems. The functions most used in hospital models and their influence on the quality of care processes are determined.